Good Corporate Governance, Free Cash Flow, dan Leverage terhadap Earning Management dengan Kualitas Audit sebagai Variabel Moderasi - Rico Nur Ilham; Debi Eka Putri; Irada Sinta; Liper Siregar; Saprudin Saprudin (Jurnal Ilmu Manajemen, 2022)
This study examines the effect of good corporate governance, free cash flow, and leverage on earnings management with audit quality as a moderating variable in mining companies listed on the Indonesia Stock Exchange from 2015 to 2019. This study used secondary data from financial statements of mining companies on the Indonesia Stock Exchange accessed at www.idx.co.id. The data analysis method used was multiple linear regression methods with the help of Eviews. The results show that good corporate governance, free cash flow, and audit quality have an insignificant effect on earnings management, and leverage significantly adversely affects earnings management. The results also show that audit quality is a variable that can moderate the relationship between good corporate governance and earnings management but cannot moderate the relationship between free cash flow and earning management and leverage with earnings management. Companies must continue to manage the company well in order to achieve company goals